Transverse strength measurements of repaired acrylic resin modified with different surface treatments (Mustansiria Dental Journal, 2018)
Aim: the purpose of this study was to evaluate the effect of chemical and mechanicalsurface treatments on repaired acrylic resin in terms of transverse strength.Materials and methods: seventy acrylic specimens were fabricated and divided into7 groups according to kind of reinforcement materials. Thesespecimenswere cut inthe mid and a space of 3 mm was created. The repair was done with varioussurface treatments and specimenswere then subjected to loads till fracture. Datawere analysed and compared via ANOVA and Tukey tests.Results: the transverse strength of repaired acrylic resin had been influenced by thetype of surface treatment used.The repaired samples withglass fibers,stainless steelwire and monomerimproved significantly the bond strength than untreated group(P